ANALYSIS OF DATA JOURNALISM IMPLEMENTATION: CHALLENGES AND OPPORTUNITIES IN MODERN MEDIA - Jafaruddin, Jafaruddin; Zahari, Zahari (Program Studi Sosiologi Universitas Malikussaleh, 2024)
Data journalism has transformed the way media reports news, shifting from reliance on sources' opinions to a data-driven approach. In today's information era, this method is essential for enlightening the public. Technological advancements have made it easier for journalists to implement data journalism, but they also present challenges, such as limited access to data and a lack of analytical skills among journalists. This research analyzes the application of data journalism in various media organizations, identifying challenges and uncovering opportunities. The methods used include interviews with journalists, academics, and ethics experts. The findings indicate significant challenges, but also opportunities to enhance news quality, public trust, and reader engagement. The research recommends the need for intensive training in data analysis and the application of strict ethical standards. Thus, data journalism can be an effective tool in addressing challenges in the digital era and contributing positively to media development.